Geometry of biofilm carriers: A systematic review deciding the best shape and pore size - Al-Amshawee, Sajjad; Mohd Yusri, Mohd Yunus (Elsevier, 2021)
Shapes and pores of biofilm carriers play a major role in deciding fluidization efficiency, biomass immobilization and removal efficiency. However, little is known about their impact on the efficiency of bioremediation. This review study sheds light on the function of carrier geometry (i.e., pores and shapes) on the bioremediation productivity, where the wrong selection of such carrier geometry may prevent attached microbes at the core from accessing nutrients. It was found that the ideal porous biofilm carrier undoubtedly has to be spherically shaped, with ridges on its surfaces, and characterized by larger than 1 mm of irregular pore size openings. The irregular pore openings provide various environments to culture various cells, develop uneven biofilm, and retain different sizes of cells and biomass. The findings challenge current literature knowledge and commercial strategies that have chosen the surface area as the critical factor.